An assured deletion scheme for encrypted data in Internet of Things. (February 2019) - Mu, Haibing; Li, Yuanyuan
With the development of Internet of Things, heterogeneous data from all kinds of sensors are processed and stored in the cloud server provider. Cloud can be regarded as one of the important layers in the Internet of Things architecture and Internet of Things is the biggest customer of the cloud. As to the security in the Internet of Things, encryption is one of the important mechanisms to achieve confidentiality of the data. However, data encryption introduces new challenges for its assured deletion in cloud, which becomes crucial for big data storage and processing in cloud for Internet of Things. Most existing solutions of cloud data assured deletion only delete the key while the ciphertext is still intact. On the other hand, the decryption time of the user increases with the size of data in the solutions. In this article, we propose a novel assured deletion scheme over encrypted cloud data based on the idea of uploading by sampling slice and outsourcing the decryption of ciphertext policy attribute–based encryption. The analysis and simulation results show that our scheme is secure and efficient, especially on reducing the decryption time of the user. We also designed a ciphertext deduplication scheme based on this scheme and explained its flow.